Direct-Acting Antiviral Hepatitis C Treatment Cascade and Barriers to Treatment Initiation Among US Men and Women With and Without HIV. (3rd November 2020) - Haley, Danielle F; Edmonds, Andrew; Ramirez, Catalina; French, Audrey L; Tien, Phyllis; Thio, Chloe L; Witt, Mallory D; Seaberg, Eric C; Plankey, Michael W; Cohen, Mardge H; Adimora, Adaora A
Abstract: Background: People with HIV are disproportionately coinfected with hepatitis C virus (HCV) and experience accelerated liver-related mortality. Direct-acting antivirals (DAAs) yield high sustained virologic response (SVR) rates, but uptake is suboptimal. This study characterizes the DAA-era HCV treatment cascade and barriers among US men and women with or at risk for HIV. Methods: We constructed HCV treatment cascades using the Women's Interagency HIV Study (women, 6 visits, 2015–2018, n = 2447) and Multicenter AIDS Cohort Study (men, 1 visit, 2015–2018, n = 2221). Cascades included treatment-eligible individuals (ie, HCV RNA-positive or reported DAAs). Surveys captured self-reported clinical (eg, CD4), patient (eg, missed visits), system (eg, appointment access), and financial/insurance barriers. Results: Of 323/92 (women/men) treatment eligible, most had HIV (77%/70%); 69%/63% were black. HIV-positive women were more likely to attain cascade outcomes than HIV-negative women (39% vs 23% initiated, 21% vs 12% SVR); similar discrepancies were noted for men. Black men and substance users were treated less often. Women initiating treatment (vs not) reported fewer patient barriers (14%/33%). Among men not treated, clinical barriers were prevalent (53%). Conclusions: HIV care may facilitate HCV treatment linkage and barrier navigation. HIV-negative individuals, black men, and substance users may need additional support. Clinical trials registration: NCT00000797 (Women's Interagency HIV Study); NCT00046280 (Multicenter AIDS Cohort Study). Abstract : People with HIV were more likely to receive HCV treatment than people without HIV. HIV care may facilitate HCV treatment linkage and barrier navigation. HIV-positive individuals, black men, and people who use alcohol and other drugs may need additional support.